To Determine the Frequency of H. Pylori Infection and its Association with Lymphoid Follicle Formation in Gastritis - Parween, Salma; Mehboob, Shafaque; Sultan, Binish Arif; Irshad, Zareen; Shaikh, Asma; Langhani, Suresh Kumar (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To evaluate the frequency of H-pylori infection and lymphoid follicle formation in gastric biopsies. Methodology: The presented study was a cross-sectional and performed in PNS Shifa hospital, Karachi from November 2013 to May 2014. Gastric biopsies of 122 patients of age between (15 to 65), male and female with complain of mild to severe gastritis were included, while patients on treatment or known case of carcinoma, inadequate, unfixed and crushed biopsies were excluded. Detail histopathological examination was carried out. The frequencies of H. pylori infection and lymphoid follicles formation were noticed along with the history of the patients. Results: In the present study, out of 122 cases, 46(37.70%)were between 15-40 years of age while 76(62.30%) were in between 41-65 years of age, mean age was calculated as 44.39+12.29 years, 63(51.64%) were male and 59(48.36%) were females. Frequency of H-pylori infection and lymphoid follicles in gastric biopsies were calculated as 81(66.39%) and 49(40.16%) respectively. Significant association of H. pylori infection and lymphoid follicle formation was seen. (P-value= 0.03, by Chi-square test) Conclusion: This study concludes that the frequency of H-pylori infection and lymphoid follicle formation (precursor of MALT lymphoma) in gastric biopsy is significantly associated and this study will help in early detection of positive cases for appropriate antibiotic therapy and H-pylori eradication therapy, thus saving the patient from developing MALT Lymphoma and other malignancies. Keywords: H. pylori, Lymphoid follicle, MALT Lymphoma